PEMANFAATAN MEDIA DIGITAL DALAM PENGINJILAN DI GBI ROCK JAKARTA - Rolando, Richard; Nugroho, Siswo; Pieter, Roy; Limanto, David (STT KINGDOM BALI, 2025)
Evangelism is a central mission of the church to proclaim the Good News of salvation through Jesus Christ to all people. In the digital era and post-COVID-19 pandemic context, digital media has emerged as a strategic tool that enables the rapid and far-reaching dissemination of the Gospel across geographical boundaries. This study aims to describe how GBI ROCK Jakarta utilizes digital media in its evangelistic efforts. Using a qualitative descriptive method, data was collected through interviews with seven satellite pastors of GBI ROCK Jakarta, all of whom have a theological academic background. The findings reveal that these pastors fully understand the purpose of evangelism and have applied various methods, both traditional and digital, including the use of platforms such as WhatsApp, Instagram, Facebook, and YouTube. Digital media has proven effective in reaching a broader audience and extending the church’s evangelistic reach. However, it also presents limitations, such as reduced personal interaction and challenges in follow-up engagement. This study affirms that digital media is not merely a tool for communication, but a vital means of Gospel proclamation relevant to contemporary global challenges